Biblical Genealogies: A Form-Critical Analysis, with a Special Focus on Women - Klip, Hedda (Oudtestamentische Studiën, Old Testament Studies, 2022)
This book is the first comprehensive study completely dedicated to all biblical genealogies. It provides a form-critical analysis of these genealogies and defines basic patterns and deviations. Helpful charts guide you towards the distinctive characteristics of these patterns. The last chapter of the book summarises all genealogical information on women in their different roles as daughters, sisters, and wives. The book includes a short comparison to the presence of women in the genealogies in the Liber Antiquitatum Biblicarum.